Predictors of visual acuity and genotype-phenotype correlates in a cohort of patients with Stargardt disease. Issue 4 (23rd January 2014) - Miraldi Utz, Virginia; Coussa, Razek Georges; Marino, Meghan J; Chappelow, Aimee V; Pauer, Gayle J; Hagstrom, Stephanie A; Traboulsi, Elias I
Abstract : Purpose: To assess the genotypic diversity in patients with Stargardt disease and to characterise epidemiological and genotypic predictors of phenotype. Methods: Retrospective, cross-sectional study of 112 patients with Stargardt disease. We evaluated the correlation between age at presentation, best-corrected visual acuity (BCVA), and ABCA4 genotypes. Results: Mean age at presentation was 30±16 years (range 6–78 years) for the 112 patients of 104 families. 98 of 90 families had a probable molecular diagnosis. We found that BCVA is not related to age of presentation in a linear or polynomial manner; that BCVA of patients presenting in the first decade was significantly worse than those presenting in later decades (p=0.04); that patients who harboured two or more mutations presented earlier and had worse BCVA than those with no or 1 mutation identified by any method of testing (n=112, p=3.29×10 −6 ) or by full sequencing (n=32, p=0.02); that 16 patients with c.5882G>A allele demonstrated better BCVA than the remaining patients (p=0.01); and that 10 patients with the c.5461-10T>C mutation presented earlier (p=0.02×10 −5 ) and had more severe disease. Conclusions: Epidemiological and genotypical findings portend visual prognosis in patients with Stargardt disease. Select sequence variations in ABCA4 may confer a specific phenotype. The present data will help in assessing patients for emerging therapies.